Combination of tramadol, diazepam, xylazine and ketamine as anesthetic protocol for canine ovariohysterectomy in sterilization campaigns and its effects on vital signs - Huayta Huanca, Jhon David (2017)
The study aimed to determine changes in respiratory and heart rate, pulse, saturation of oxygen, temperature and blood pressure caused by the combination of tramadol, diazepam, xylazine and ketamine during canine ovariohysterectomy for possible use in sterilization campaigns. Ten bitches between 10 months and 6 years of age of different breeds and sizes, clinically healthy, with hemogram and leucogram normal and classified as ASA I and II, were subjected to elective surgery ovariohysterectomy using the same anesthetic protocol. Physiological data was recorded during the six stages of the anesthetic-surgical procedure. Heart rate and pulse were within normal levels. Three patients presented tachypnea during maintenance. Episodes of mild hypoxia were observed. Body temperature showed a gradual decline. All patients presented hypertension during maintenance and the end of the surgery. There were no complications during the anesthetic recovery. The anesthetic protocol is inexpensive and despite cases of hypertension, it can be used to perform ovariohysterectomy in canine sterilization campaigns for patients ASA I and ASA II.